Świrszczyńska (za)poznana? Feministyczne odkrywanie poetki - Biedrowska, Adriana (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
This paper encourages to renew a reflection on poetry of Anna Świrszczyńska – a well-known but also unknown author. It discusses the subject of motherhood in this poetry (pregnancy, childbirth, puerperium) and shows, how relevant Świrszczyńska’s works still are. Her poetry is nowadays continued not only by others women writers and poets, but also – or maybe: first of all – by feminist opinion journalism.